2007
DOI: 10.1002/jez.433
|View full text |Cite
|
Sign up to set email alerts
|

Myosin regulatory light chain expression in trout muscle

Abstract: Muscle's contractile properties can vary along different trajectories, including between muscle fiber types, along the body (within a muscle fiber type), and between developmental stages. This study explores the role of the regulatory myosin light chain (MLC2) in modulating contractile properties in rainbow trout myotomal muscle. Rainbow trout show longitudinal variations in muscle activation and relaxation, with faster contractile properties in the anterior myotome. The expression of two muscle proteins, trop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…The expression patterns of the fish MyHC and MLCs are environmentally and developmentally regulated [31][32]. In this study we showed that MLC1 and MLC3 were differentially expressed in developing somites and skeletal muscles of fish embryos.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The expression patterns of the fish MyHC and MLCs are environmentally and developmentally regulated [31][32]. In this study we showed that MLC1 and MLC3 were differentially expressed in developing somites and skeletal muscles of fish embryos.…”
Section: Discussionmentioning
confidence: 59%
“…The MLCs exist in two forms, the essential light chain (MLC1/3) and the regulatory light chain (MLC2) [3]. The relative content of MyHC and MLC in muscle fiber determines the muscle properties.…”
Section: Introductionmentioning
confidence: 99%
“…Myosin, the major protein component of muscle tissue, is a hexameric protein composed of two heavy chain (myosin heavy chain, MyHC ) subunits with molecular mass c. 220 kDa (kilo‐Dalton) and four light‐chain subunits c. 16–20 kDa, that are the primary determinants of contractile performance (Kikuchi et al , 1999; Bryson‐Richardson et al , 2005; Nihei et al , 2006). The myosin light chains ( MLC ) belong to the EF‐hand (helix‐loop‐helix) superfamily (Trybus, 1994) and the four MLC s are classified into two classes: two essential light chains released from heavy chains by alkaline treatment and the other two regulatory light chains dissociated with the alkali and dinitrobenzoic acid (DTNB), which are all expressed in slow and fast muscles (Ochiai et al , 1990; Donato et al , 2008). These two types of essential light chain, MLC1 and MLC3 , are ontogenetically differentially expressed from lower vertebrates to higher vertebrates (Trybus, 1994; Thiebaud et al , 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The complementary DNA (cDNA) clone analysis indicates a similar situation in the amphibian Xenopus laevis (Periasamy et al , 1984). The DTNB‐removable light chain, MLC2 , also known as myosin regulatory light chain ( MRLC or RLC ), has many isoforms depending on its distribution (Lowey & Trybus, 1995; Donato et al , 2008). In smooth muscle, MLC2 is phosphorylated at Thr18 and Ser19 by myosin light chain kinase (MLCK) in a Ca 2+ –calmodulin‐dependent manner (Ikebe & Hartshorne, 1985; Ikebe et al , 1998, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation